The 1990s “Kutaisi Wave”: Music and Youth Movement in a Postindustrial Periphery - Ninoshvili, Lauren (Current Musicology, 2011)
In this paper I treat popular music as a lens for exploring the intersections of place and postsocialist youth identity in Kutaisi in the early-mid 1990s, bearing in mind throughout the noticeable cultural rivalry between Kutaisi and Georgia’s political capital. Kutaisi-based musicians maintain that Georgia’s rock and alternative music industry began in their hometown in the final years of socialism and spread from there to Tbilisi. After the civil war that spoiled the initial euphoria of independence in 1991, a dynamic Kutaisi-based popular movement mobilized locally produced rock, punk rock, and related genres to publicly articulate disaffection with the conditions of postsocialism. While the dominant discourse on Kutaisi dismisses this movement as inconsequential or even a national disgrace, those who were involved consider it the first and only post-Soviet manifestation in a long genealogy of forms of liberal, cosmopolitan consciousness to emerge from Kutaisi. The latter also maintain that it marked an instance of anti-establishment grassroots social organizing, which is relatively rare in modern Georgian memory. While some participant-observers assert that the popular music produced in Kutaisi in this period was characterized by”uncompromising protest” (Gabunia 2005), I argue that the movement’s greater social significance lay in its clustering of a whole repertoire of music-centered activities to create a platform for youth-centered solidarity in the face of ubiquitous social and economic uncertainty. Many of the songs also served as vehicles for civic activism and/or resistance to authority. What were the aesthetics of difference salient to young Kutaisi musicians and their audiences in this period? How did these articulate with a local sense of place in the context of a contested national cultural geography? My study emphasizes the importance of locality within the bounds of the nation-state as a site of identity struggle in the postsocialist space.